P42 Comparison of the clinical outcomes after de-novo heart transplantation between adults with and without congenital heart disease. (2nd March 2016) - Taylor, A; Lannon, J; Taylor, R; Banner, N; Thompson, R; Al-Attar, N; Parameshwar, J; Venkateswaran, RV; Crossland, D; Dominguez, T; Burch, M
Abstract : Background: There is a little published research in the United Kingdom comparing the clinical outcomes after de-novo heart transplantation between adults with and without congenital heart disease. This is of particular importance with the population of congenital heart disease (CHD) patients requiring heart transplantation in adulthood rapidly expanding. There is controversy over organ allocation to adults with CHD (ACHD) as they may have higher operative risk. Methods: Adults (aged > 16 years) undergoing a first heart transplant between 1995–2014 were identified in the UK Transplant Registry held by NHS Blood and Transplant (NHSBT). Registration-, operative- and post-transplantation-related clinical data  were compared between ACHD and other adult de-novo heart transplant recipients. Post-transplant survival was compared between the groups using the Kaplan-Meier method. Further survival analysis was restricted to the ACHD sub-group registered between 2005–2014 comparing the impact of complex (single ventricle) morphology and previous procedure on long-term survival. Results: Of 3026 adults who underwent de-novo heart transplantation, 134 (4.43%) adult recipients had CHD (median age at transplantation 30 years; 40.3% female). Despite ACHD recipients having lower 90-day survival (79.5% vs. 86.6%; p = 0 .02), post-transplantation survival at 1-year (ACHD: 77.2% vs. non-ACHD: 82.2%), 5-years (ACHD: 67.7% vs. non-ACHD: 72.1%) and 10-years (ACHD: 57.4% vs. non-ACHD: 57.9%) was not significantly different between groups. Compared with those without CHD, the ACHD recipients had longer waiting times (86 vs. 52 days, p = 0 .04) and hospital stays (27 vs. 22 days; p = 0 .003). Creatinine clearance was significantly lower in ACHD patients at 3 (120 vs. 128; p = 0 .01) and 12 months (120 vs. 136; p < 0 .0001) follow-up compared to other adult recipients. The number registered as urgent or receiving transplantation with an urgent status was not significantly different between the groups. Between 2005–2014, there were 63 ACHD with two ventricles and 76 ACHD with a single ventricle registered for heart transplantation (univentricular cohort: Fontan (n = 38); Glenn (n = 29); Blalock-Taussig (n = 8); no surgery (n = 1)). There were 74 ACHD de-novo heart transplantations between 2005–2014. Post-transplantation survival data was available for 61/74 (univentricular (n = 25) vs. biventricular (n = 36)). One-year post-transplantation survival was marginally better in univentricular ACHD (95.9% vs. 93.5%), although this was not significantly different ( p = 0 .4). Fontan survival was 89.7% at 4-years post-transplantation. Conclusions: Despite ACHD having poorer 90-day survival, long-term post-transplantation survival was comparable between ACHD de-novo heart transplant recipients and those with other diagnoses. Single ventricle patients had similar survival to two ventricle ACHD transplant recipients.